Generalized Point Reactor Kinetics - André Luiz Yoshio Valentim Oyama; Adilson Costa da Silva; Alessandro da Cruz Gonçalves; Aquilino Senra Martinez (Brazilian Journal of Radiation Sciences)
In this paper, we are proposing a generalized analytical solution to the point reactor kinetics equations for six groups of delayed neutron precursors for both conventional and subcritical equations. The methodology presented aims to obtain an analytical solution using the similarity transformation technique. This solution will make it possible to evaluate the behavior of the nuclear reactor power as a function of time, for a given constant reactivity inserted in the reactor core, in a very simple way and without computational effort, compared to numerical solutions. The results obtained will be compared with reference methods to validate the methodology presented in this paper.